2018
DOI: 10.1177/0961203317751860
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine patterns in plasma of patients with systemic lupus erythematosus and fever

Abstract: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with various clinical manifestations and serologic markers. In this study, we analyzed nine polyamine (PA) profiles of plasma from patients with SLE and healthy controls (HCs), and the relationship between the PA profiles and disease activity. PA alterations in plasma of 44 patients with SLE and fever were investigated using gas chromatography mass spectrometry (GC-MS) in selected ion monitoring mode using N-ethoxycarbonyl/ N-pentafluoropropio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Here, we highlight its critical role in IFN-related autoimmune diseases. Consistent with this, spermidine and spermine in plasma of patients with SLE and fever were found to be decreased (Kim et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…Here, we highlight its critical role in IFN-related autoimmune diseases. Consistent with this, spermidine and spermine in plasma of patients with SLE and fever were found to be decreased (Kim et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, increased polyamines may downregulate interleukin‐2 in RA . Recently, Kim et al reported that systemic lupus erythematosus (SLE) patients had decreased plasma SPD, SPM, and NSPD and increased plasma CAD levels. However, little is known about the relationship between polyamine metabolites and AITD.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with 1% DFMO in water given to NZB/W mice (a lupus-prone model) reduced IgG and IgA levels in the mice and reduced spermidine and putrescine levels suggesting the inhibition of ODC as a promising avenue for SLE therapeutics [69]. As for SLE in humans, Kim et al reported differences in plasma polyamine levels of SLE patients compared to controls with SLE patients showing significant decreases in spermine, spermidine, acetylspermidine, and acetylcadaverine while there was an increase in cadaverine [70]. Thomas et al reported greater binding of SLE anti-DNA antibodies in the presence of spermine, suggesting a possible role of spermine in the autoantigen creation [71].…”
Section: Polyaminesmentioning
confidence: 99%